2009
DOI: 10.4319/lom.2009.7.595
|View full text |Cite
|
Sign up to set email alerts
|

In vivo DMSP‐biosynthesis measurements using stable‐isotope incorporation and proton‐transfer‐reaction mass spectrometry (PTR‐MS)

Abstract: Assessing turnover rates of dimethylsulfoniopropionate (DMSP), precursor of the climate-active gas dimethylsulfide (DMS), under different environmental conditions is fundamental to accurately modeling the marine sulfur cycle. Current gas chromatographic methods only provide net results of all processes acting on the different sulfur pools and are unable to measure fluxes, leaving room for speculation on the controlling factors and magnitudes of turnover processes. Here we present a new method in which stable i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 40 publications
1
42
0
Order By: Relevance
“…Determination of de novo DMSP synthesis rates (µDMSP) was carried out according to Stefels et al (2009). Incorporation of 13 C into DMSP was determined by proton transfer reaction mass spectrometry (PTR-MS) of DMS swept from the 20 mL vials and recorded as mass 63, 64 and 65 of protonated forms of 12 C-DMS, 13 C-DMS 34 S-DMS, respectively.…”
Section: Dmsp Synthesis and Production Ratesmentioning
confidence: 99%
See 2 more Smart Citations
“…Determination of de novo DMSP synthesis rates (µDMSP) was carried out according to Stefels et al (2009). Incorporation of 13 C into DMSP was determined by proton transfer reaction mass spectrometry (PTR-MS) of DMS swept from the 20 mL vials and recorded as mass 63, 64 and 65 of protonated forms of 12 C-DMS, 13 C-DMS 34 S-DMS, respectively.…”
Section: Dmsp Synthesis and Production Ratesmentioning
confidence: 99%
“…A weighted average approach that gives most weight to the initial points of the exponentially decreasing DMS peak was used to calculate the mass ratio 64 MP t for each sample at each time point. The mass ratio progress method described by Stefels et al (2009) was applied to calculate µDMSP. This applied information from culture-based studies of Emiliania huxleyi to calculate the isotope fractionation factor (Stefels et al, 2009).…”
Section: Dmsp Synthesis and Production Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…This procedure, applicable to any system, may serve as a template to study the sub-cellular localization and identification of other small and highly diffusible molecules. In addition, similarly to other recent stable isotope approaches (Stefels et al, 2009), our method may be used to quantify the production rate of DMSP at the single cell level. We confirmed that 34 S-DMSP was the main organic sulfur compound within the algal cells and we subsequently localised large quantities of the sulfur tracer 34 S in algal vacuole, cytoplasm and chloroplasts.…”
Section: Resultsmentioning
confidence: 96%
“…These include X-ray microanalysis (Heldal et al 1985), modified isotope ratio mass spectrometry (IRMS) (Eek et al 2007) and secondary ion mass spectrometry (SIMS) (Orphan & House 2009). The latter 2 approaches potentially provide estimates of stable isotopic composition of small sample sizes, opening up the potential to combine FACS-GC based estimates of intracellular DMSP content in specific groups with measures of their metabolic activity, including possibly in vitro DMSP synthesis (Stefels et al 2009). One advantage of the mechanical-FACS mechanism is the capability to use radioisotope tracers to determine metabolic activity, including DMSP uptake, in specific components of microbial populations , Vila-Costa et al 2006 without the problems associated with production of radioactive aerosols that droplet-FACS mechanisms potentially produce.…”
Section: Discussionmentioning
confidence: 99%